Multidrug Resistance in Pseudomonas Aeruginosa and Evaluation of Probiotics as Alternative Therapeutic Candidates - Mahdi, Dunya Talib; Hassoon, Rasha Amer; Jaleel, Israa (American Journal of Biology and Natural Sciences, 2025)
Pseudomonas aeruginosa is a critical opportunistic pathogen and a major cause of hospital-acquired infections. Its remarkable ability to develop multidrug resistance (MDR) has become a serious global health concern, especially in burn patients and immunocompromised individuals (Wang et al., 2024; Ramatla et al., 2025). This study aimed to investigate the prevalence and resistance profiles of P. aeruginosa isolates from clinical specimens and to evaluate the inhibitory potential of Lactobacillus rhamnosus and Lactobacillus acidophilus (Artini et al., 2024; Al-Janabi et al., 2025). A total of 150 clinical samples (burn wounds, pus, urine, and sputum) were analyzed. Sixty isolates (40.0%) were confirmed as P. aeruginosa. Resistance rates were highest against ceftazidime (83.3%) and ciprofloxacin (78.3%), while imipenem (40.0%) and amikacin (36.7%) retained partial effectiveness (Kim et al., 2024). Both probiotics inhibited MDR isolates, with L. rhamnosus producing significantly larger inhibition zones (17.8 ± 2.1 mm) compared with L. acidophilus (13.2 ± 1.7 mm; p < 0.05). In conclusion, the study confirms the alarming resistance levels of P. aeruginosa and highlights the promising potential of probiotics as adjunctive antimicrobial strategies.